A comprehensive analysis of allele-specific expression and transcriptomic profiling in pig limbic and endocrine tissues - Iqbal, Muhammad Arsalan; Hadlich, Frieder; Reyer, Henry; Oster, Michael; Trakooljul, Nares; Wimmers, Klaus; Ponsuksili, Siriluck (Frontiers in Molecular Neuroscience, 2025)
IntroductionStress involves complex interactions between the brain and endocrine systems, but the gene-level processes and genetic factors mediating these responses remain unclear. This study investigates gene expression patterns and allele-specific expression (ASE) in key limbic, diencephalon and endocrine tissues to better understand stress adaptation at the molecular level.MethodsWe performed RNA sequencing on 48 samples from six distinct tissues: amygdala, hippocampus, thalamus, hypothalamus, pituitary gland, and adrenal gland. These tissues were categorized into three functionally and anatomically distinct groups: limbic (amygdala, hippocampus), diencephalon (thalamus, hypothalamus), and endocrine (pituitary, adrenal). Differential expression analyses were conducted both between individual tissues and across these tissue groups. Weighted Gene Co-expression Network Analysis (WGCNA) was applied exclusively at the tissue group level to identify group-specific gene networks. Allele-specific expression (ASE) was analyzed at the individual tissue level to capture cis-regulatory variation with high resolution.ResultsThirty-three candidate genes were differentially expressed across all tissues, indicating a core set involved in stress responses. Weighted Gene Co-expression Network Analysis revealed limbic and diencephalon modules enriched in neural signaling pathways such as neuroactive ligand-receptor interaction and synaptic functions, while endocrine modules were enriched for hormone biosynthesis and secretion, including thyroid and growth hormone pathways. Over 1,000 genes per tissue showed ASE, with 37 genes consistently colocalized. Ten of these displayed differences in allelic ratios, with seven (PINK1, TTLL1, SLA-DRB1, HEBP1, ANKRD10, LCMT1, and SDF2) identified as eQTLs in pig brain tissue within the FarmGTEx database.ConclusionThe findings reveal significant genetic regulation differences between brain and endocrine tissues, emphasizing the complexity of stress adaptation. By identifying key genes and pathways, this study provides insights that could aid in enhancing animal welfare and productivity through targeted modulation of stress-related molecular pathways.